brucellosis as trigger for autoimmune hepatitis in susceptible individual - AL-Obeidy, Eman Sh. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Autoimmune hepatitis (AH) is a rare chronic liver disease of unknown etiology,